Contrast-enhanced ultrasound manifestations of renal masses undetectable on conventional ultrasound - Tao, Lingling; Fan, Jinfang; Zhan, Weiwei; Li, Weiwei; Lu, Jian; Yang, Nanan; Ma, Binbin; Zhou, Wei (Frontiers in Oncology, 2022)
This study aimed to retrospectively analyze the features of contrast-enhanced ultrasound (CEUS) of renal masses that cannot be detected by conventional ultrasound (CUS).The data of 264 patients who underwent CEUS for renal lesions from January 2016 to December 2019 were retrieved. Of these, 16 patients with renal masses which were not detected by CUS were included in the final analysis. The corresponding characteristics of CEUS were evaluated, including intensity of enhancement, homogeneity, wash-in and wash-out patterns, and perilesional rim-like enhancement. Among the 16 patients, 10 patients had clear cell renal cell carcinoma (ccRCC), 6 patients had urothelial carcinoma of renal pelvis (UCRP). Compared with the location on non-enhanced computed tomography (CT) scan, all tumors were detected on CEUS. Most(7/10) ccRCCs appeared hyper-enhancement, homogeneous enhancement, synchronous-in and no perilesional rim-like enhancement. Most(4/6) UCRPs appeared iso-enhancement, slow-in, fast-out and no perilesional rim-like enhancement. CEUS may be helpful in the diagnosis and differential diagnosis of renal tumors which were not observed on CUS, and it might be an alternative method for some patients when contrast enhanced computed tomography (CECT) or magnetic resonance imaging(MRI) cannot be performed.